Gene Expression Profiling Of The Carbon Assimilation And Virulence Factors Of Candida Albicans In Different Carbon Monosaccharides Sources - Lok, Bronwyn (2024)
One of the virulence factors of candida albicans is its metabolic flexibility, which enables it to survive and colonise diverse niches in the host. The aim of this study is to investigate the effects of the different carbon sources available in its host niches on the growth, fitness, and pathogenicity of the fungus. The effects of different carbon sources — glucose, fructose, and galactose, as well as their resistance towards the antifungal drug fluconazole, were investigated through growth studies, gene expression profiling, and real-time quantitative pcr (qpcr). The growth of the c. Albicans cells were significantly slowed when galactose was used as their carbon source compared to the cells grown in glucose. Fluconazole was also found to have a stronger antifungal effect towards the cells grown in glucose and fructose compared to those grown in galactose. From the gene expression profiling, it was found that c. Albicans undergoes a massive metabolic reorganization when grown on fructose and galactose compared to when it is grown in glucose, leading to changes in the expression of various carbon metabolic genes such as icl1 (0.86 in fructose, -5.67 in galactose), mls1 (1.08 in fructose), and mdh1 (0.93 in fructose, -1.14 in galactose). Finally, genes with alternative splicing and predicted novel transcripts were identified from the c. Albicans cells grown in the different condition.